IMPROVING THE COMPETITIVENESS OF MSMES THROUGH THE IMPLEMENTATION OF HUMAN RESOURCE MANAGEMENT INFORMATION SYSTEMS AND DIGITAL MARKETING STRATEGIES IN BANGGAI REGENCY, CENTRAL SULAWESI ISLANDS - Dg.Liwang, Asmita Wulansari; Doloan, Eef Saifullah; Izaak, Fitri Devi Lestari; Saudin, La (Yayasan Education and Social Center, 2025)
This community service activity aims to improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) through the implementation of a Human Resource Management Information System (SIM SDM) and digital marketing strategies in Banggai Kepulauan Regency, Central Sulawesi. The main problems faced by partner MSMEs include weak human resource management, low digital literacy, and limited market access due to the geographical conditions of the archipelago. This activity was carried out for one month in November 2025 using a participatory approach through training, mentoring, and direct practice. The activity methods included needs assessment, simple SIM SDM training, social media and marketplace-based digital marketing training, and implementation and evaluation assistance. The results of the activity showed an increase in understanding and skills of MSME actors in more structured HR management, increased utilization of digital platforms for marketing, and positive changes in business managerial and marketing practices. The synergy between strengthening internal management and digital marketing has been proven to improve operational efficiency and expand the market reach of MSMEs. This activity is expected to become a sustainable service model and can be replicated in other archipelago regions with similar characteristics to support the digital transformation of MSMEs.